The ultimate college cookbook : easy, flavor-forward recipes for your campus (or off-campus) kitchen - Granof, Victoria, 1958- (Clarkson Potter/Publishers, 2020)
"Students will discover the joy and simplicity of cooking for themselves with 60 recipes for easy, delicious meals that can easily be made in any dorm room or shared apartment. The Ultimate College Cookbook offers sixty recipes for everything from breakfast to weeknight cooking and weekend gatherings, on-campus or off. Each dish is designed to be cooked in a dorm-friendly appliance, including microwaves, toaster ovens, electric burners, rice cookers, and slow cookers"--